Contemporary Issues in Current Account Operations in Pakistani IBs - Sharia Compliant Solution - Sheikh Muhammad Ishtiaq; Wasie Fasih Butt; Fahad Ahmed Qureshi; Mubeen Butt (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2018)
Contemporary Sharia scholars have three stances about the Current Account Operations in Pakistani Islamic Banks (IBs) i.e., (i) Ijarah based contract (ii) Wadi’ah based contract, and (iii) Qard based contract. This paper is an attempt to delve into the root causes of the differences of scholars and to find the Sharia-compliant solution acceptable for all. Descriptive as well as applied approaches are used in this paper. Clearing of ambiguity on this issue may result in twofold benefits: from the public point of view, it would satisfy practising Muslims which may result in form of huge deposits in this account (ii) from IBs viewpoint the Current Account is a bonus deposit.